2020
DOI: 10.1302/2633-1462.110.bjo-2020-0129
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review assessing the evidence for the use of stem cells in fracture healing

Abstract: Aims Bone demonstrates good healing capacity, with a variety of strategies being utilized to enhance this healing. One potential strategy that has been suggested is the use of stem cells to accelerate healing. Methods The following databases were searched: MEDLINE, CENTRAL, EMBASE, Cochrane Database of Systematic Reviews, WHO-ICTRP, ClinicalTrials.gov, as well as reference checking of included studies. The inclusion criteria for the study were: population (any adults who have sustained a fracture, not includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…However, harvesting ABGs imparts additional morbidity. Furthermore, a recent systematic review concluded that, despite ongoing research, there is currently insufficient evidence to elucidate the utility of biologically active bone grafts in fracture healing [38] . Indeed, consensus indicates that synthetic bone grafts may provide viable alternative void filler in the setting of tibial plateau fractures [5,10,30,34,[39][40][41][42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…However, harvesting ABGs imparts additional morbidity. Furthermore, a recent systematic review concluded that, despite ongoing research, there is currently insufficient evidence to elucidate the utility of biologically active bone grafts in fracture healing [38] . Indeed, consensus indicates that synthetic bone grafts may provide viable alternative void filler in the setting of tibial plateau fractures [5,10,30,34,[39][40][41][42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…45 Furthermore, a recent systematic review concluded that, despite ongoing research, there is currently insufficient evidence to elucidate the utility of biologically active bone grafts in fracture healing. 46 Indeed, consensus indicates that synthetic bone grafts may provide a viable alternative void filler in the setting of tibial plateau fractures. [31][32][33][34][35][36][37]40,[47][48][49] This meta-analysis represents the most contemporary synthesis of high-quality (Oxford Centre for Evidence-Based Medicine, OCEBM, Level 1), randomizedcontrolled literature comparing synthetic and autologous bone grafts for tibial plateau fractures, and supersedes a previous systematic review containing lower-level literature.…”
Section: Discussionmentioning
confidence: 99%
“… 45 Furthermore, a recent systematic review concluded that, despite ongoing research, there is currently insufficient evidence to elucidate the utility of biologically active bone grafts in fracture healing. 46 Indeed, consensus indicates that synthetic bone grafts may provide a viable alternative void filler in the setting of tibial plateau fractures. 31 - 37 , 40 , 47 - 49…”
Section: Discussionmentioning
confidence: 99%
“…Mott et al concluded that excellent proof to confirm the efficiency of MSCs for bone repair is nonexistent. 13 One strategy to increase MSC capability and function after transplantation in bone defects could be the use of photobiomodulation (PBM). Similarly acknowledged as low-level laser therapy, PBM is the usage of a laser to enhance curing, mitigate soreness, and decrease inflammation.…”
Section: Introductionmentioning
confidence: 99%